High-order harmonic generation driven by perfect optical vortex beams: Exploring the orbital angular momentum upscaling law - Bikash Kumar Das; C. Granados; M. Krüger; Marcelo F. Ciappina (Physical Review Research)
Orbital angular momentum (OAM) light beams for high-order harmonic generation (HHG) provide an additional degree of freedom to study the light-matter interaction at ultrafast timescales. A more sophisticated configuration is a perfect optical vortex (POV) beam, a light beam with a helical wave front characterized by a phase singularity at its center and an azimuthal phase variation. POV beams are characterized by a radial profile which is independent of the OAM. Here, we study the nonperturbative process of gas-phase HHG using a linearly polarized POV beam. We observe that the harmonics are emitted with similar divergence due to the perfectness of the POV-driven harmonic generation. Furthermore, the topological charge upscaling is rigorously followed. We show that a POV beam is more advantageous than that of the Laguerre-Gaussian beam for cases where a large topological charge with a small core size is required. Our research establishes a pathway for producing bright structured extreme ultraviolet coherent radiation sources—a pivotal tool with multifaceted applications across various technological domains.